Health Learning Management at Noongan Hospital, Minahasa Regency - Mamuaja, Pricilia P; Katuuk, Deitje A; Paturusi, Achmad; Lengkong, Jeffry S. J. (Ridwan Institute, 2023)
The purpose of this study is to analyze and describe the management of health learning in the community health center at Noongan Hospital, Minahasa Regency. Health learning management is a form of learning management that focuses on nursing care services in its role as an educator. The results showed that health learning management has been carried out by Noongan Hospital, which is the current research location. The stages of health learning are through the assessment carried out by the nurse through the assessment of patients, the planning made by the nurse referring to the results of the assessment, the implementation of learning carried out by the nurse using demonstration methods, instructions and videos and evaluations carried out by the supervision team as well as periodic evaluations carried out by the head of the room. Noongan Hospital has sufficient resources in the implementation of health learning management, however, there are still weaknesses and shortcomings that need to be addressed, especially by the hospital and especially the head of the hospital so that health learning management can be more optimized to support the improvement of more optimal health service quality.